Assessing the Surface Water Quality of Ana Sagar Lake and its Bioremediation in Modified Constructed Wetland. Issue 1 (June 2021) - Syed, Zainab; Sonu, Kumar; Dongre, Aman; Sogani, Monika
Abstract: The present study evaluates the potential of an integrated Constructed Wetland and Microbial Fuel Cell (CW-MFC) in removing Chemical Oxygen Demand (COD), Total Dissolved Solids (TDS), nitrate and phosphate along with generating electricity from the polluted water of Ana Sagar Lake, Ajmer. Two vertical downward flow CW-MFCs have been investigated (with and without plant) in batch mode for a period of 12 months. The performance of CW-MFC with the plant (system A) was better than the CW-MFC without the plant (system B), both in terms of COD, TDS, nitrate and phosphate removal and electricity generation. Dracaena trifasciata plant species were used in this study. The maximum power density of 157 mW/m 2, current density of 0.65 mA/m 2, COD removal efficiency (72%), TDS reduction (74%), nitrate removal (69%) and phosphate removal (69%) were obtained with System A. The germination rate of Vigna radiata seeds was 100% with the effluent from system A. At the end of the experiment the FTIR analysis revealed the structural changes occurring on the CW-MFC media (sand) after removal of pollutants present in the lake water.